Antenatal diagnosis of placenta accreta spectrum after in vitro fertilization-embryo transfer: a systematic review and meta-analysis - Shinya Matsuzaki (Nature Portfolio, 2021)
Abstract Increasing evidence suggests a relationship between in vitro fertilization-embryo transfer (IVF-ET) and placenta accreta spectrum (PAS). Some studies have reported a lower rate of antenatal diagnosis of PAS after IVF-ET compared to PAS with spontaneous conception. This study aimed to review the diagnostic accuracy of PAS after IVF-ET and to explore the relationship between IVF-ET pregnancy and PAS. According to the PRISMA guidelines, a comprehensive systematic review of the literature was conducted through August 31, 2020 to determine the effects of IVF-ET on PAS. In addition, a meta-analysis was conducted to explore the relationship between IVF-ET pregnancy and PAS. Twelve original studies (2011–2020) met the inclusion criteria. Among these, 190,139 IVF-ET pregnancies and 248,534 spontaneous conceptions met the inclusion criteria. In the comparator analysis between PAS after IVF-ET and PAS with spontaneous conception (n = 2), the antenatal diagnosis of PAS after IVF-ET was significantly lower than that of PAS with spontaneous conception (22.2% versus 94.7%, P < 0.01; < 12.9% versus 46.9%, P < 0.01). The risk of PAS was significantly higher in women who conceived with IVF-ET than in those with spontaneous conception (odds ratio [OR]: 5.03, 95% confidence interval [CI]: 3.34–7.56, P < 0.01). In the sensitivity analysis accounting for the type of IVF-ET, frozen ET was associated with an increased risk of PAS (OR: 4.60, 95%CI: 3.42–6.18, P < 0.01) compared to fresh ET. Notably, frozen ET with hormone replacement cycle was significantly associated with the prevalence of PAS compared to frozen ET with normal ovulatory cycle (OR: 5.76, 95%CI 3.12–10.64, P < 0.01). IVF-ET is associated with PAS, and PAS after IVF-ET was associated with a lower rate of antenatal diagnosis. Therefore, clinicians can pay more attention to the presence of PAS during antenatal evaluation in women with IVF-ET, especially in frozen ET with hormone replacement cycle.